Toxic Hepatitis mortality in Rio Grande do Sul and in its Macroregions of Health, analysis from 2006 to 2015 (Research, Society and Development, 2020)
Objective: toxic hepatitis is any level of liver damage caused by drugs, medication or other substances. This research aims to describe the epidemiological profile of mortality from toxic hepatitis in the state of Rio Grande do Sul, Brazil, from 2006 to 2015. Methodology: we searched the DATASUS database looking for the number of deaths from toxic hepatitis and the total population from each region, for subsequent calculation of the death rate per 100,000 inhabitants. The analysis was divided in Health Macroregion (Valleys, South, Serra, North, Missioneira, Metropolitan and Midwest), year (2006 to 2015), sex (female and male) and age group (0-19, 20-59 and more than 60 years old). Results: a total of 31 male and 32 female deaths were identified. The difference between sexes was statistically significant (p=0.02). When comparing the 7 macroregions, Vales had the highest mortality rate and South the lowest (0.0796 and 0.0377, respectively). When comparing all macroregions per year there was no statistically significant difference (p=0.423). When comparing the age groups with the macroregions, the highest rates were found in the 60 or more years old group, but there was no statistically significant difference between the values ​​found (p = 0.416). Conclusions: we found a significant predominance of mortality in the female population, new epidemiological studies are important to characterize the pattern of distribution of the disease in our environment and, consequently, to find new forms of assistance to the patients.